PENGARUH KONSEP DIRI TERHADAP KEPERCAYAAN DIRI SISWA - Lina Novita; Sumiarsih . (Universitas Pakuan, 2021)
THE INFLUENCE OF SELF-CONCEPT ON STUDENTS' CONFIDENCEThe purpose of this study was to determine the influence of the influence of self-concept on student self-confidence. The population in this study were students in class V A and V B Baranangsiang Elementary School, Bogor City. The analysis prerequisite testing technique is in the form of a normality test, then the homogeneity test is carried out. Data that were declared normal and homogeneous were used to test the hypothesis, the results showed that there was an influence of self-concept on student self-confidence. The simple correlation regression analysis technique produces a relationship model expressed in the form of a regression equation, namely Ŷ = 59.46 + 0.43X. The results of this study are indicated by statistical analysis which produces a correlation coefficient (rxy) of 0.37. While the coefficient of determination is 0.13%. The regression analysis technique and simple correlation the effect of self-concept on students' self-confidence produces an effect that is expressed in the form of a regression equation, namely Ŷ = 59.46 + 0.43X), which means that each increase in self-concept units causes an increase in student confidence by 0.43 unit. Based on the results of the research above, it can be concluded that there is a positive influence between self-concept on the self-confidence of students in grades V A and V B of Baranangsiang State Elementary School, Bogor City, 2020/2021 academic year.